Excitation-Inhibition Balanced Neural Networks for Fast Signal Detection - Tian, Gengshuo; Li, Shangyang; Huang, Tiejun; Wu, Si (Frontiers in Computational Neuroscience, 2020)
Excitation-inhibition (E-I) balanced neural networks are a classic model for modelling neural activities and functions in the cortex. The present study investigates the potential application of E-I balanced neural networks for fast signal detection in brain-inspired computation. We first theoretically analyze the response property of an E-I balanced network, and find that the asynchronous firing state of the network generates an optimal noise structure enabling the network to track input changes rapidly. We then extend the homogeneous connectivity of an E-I balanced neural network to include local neuronal connections, so that the network can still achieve fast response and meanwhile maintain spatial information in the face of spatially heterogeneous signal. Finally, we carry out simulations to demonstrate that our model works well.